IMPLEMENTASI AKAD IJARAH PADA SISTEM UPAH BURUH PRODUKSI KAIN BATIK (STUDI KASUS DI BATIK LARISSA DAN BATIK FENO KAMPUNG BATIK PESINDON KOTA PEKALONGAN) - Safinah Annajah, Dinda; Hudaya, Fadli; Dwi Andayani, Tutut; Saebani, S (Neraca, 2023)
The study is a qualitative one it aims to answer the problems statements whether the forms of work, working time, wages, and labour devoted to the production of batik cloth in Batik Larissa and Batik Feno are in accordance with the Islamic view. The method applied here is to analyse data based on the fact obtained from the field. Meanwhile, interviews and documentations with the related parties; the owner and the labour of Batik Larissa and Batik Feno. The result obtained is the forms of work is in accordance with the existing work contracts in Batik Larissa and Feno. In the initial agreement on terms of working time, it was stated that only the contracted time was set without targeting the amount of work to be done. For the wages, the process in Batik Larissa and Feno are appropriate and equal to the enthusiasm of the workers to work. The wages have been paid daily and piece rates are given when the work has been completed. Furthermore, the workers are not forced to devote their energy excessively, only according to their ability. Based on the result stated above, it is expected for the owners in procedures of paying the workers to be always fosters mutual trust and honesty between the two parties so that it does not cause uncertainty or gharar regarding the wages and does not cause disappointment to workers. And for the wage’s procedures, it must always be adjusted to the share of participation, the type of work performed, the volume of work, and the proportion of work.   REFERENSI Skripsi Amat Saimu. (2020). berjudul Tinjauan Hukum Islam terhadap Upah Buruh Pikul di Pelabuhan Tehoku Desa Hila Kecamatan Leihitu Kabupaten Maluku Tengah. Institut Agama Islam Negri Ambon. Fatimah. (2018). Praktek Pemberian Upah Buruh Tani Karet Studi Kasus Di Desa Aek Mata Kecamatan Panyabungan Kabupaten Mandailing Natal. Institut Agama Islam Negeri Padangsidimpuan. Jusmunandar. (2020). Sistem Upah Buruh Panen Padi Dalam Perspektif Kemaslahatan Dan Keadilan ( Studi Kasus Di Kelurahan Jawi-Jawi Kecamatan Bulukumpa Kabupaten Bulukumba Sulawesi-Selatan ). Universitas Islam Negeri Alaudin Makassar. Khofifah, N. (2018). Tinjauan Hukum Islam Terhadap Sistem Pengupahan Buruh Emping Melinjo Di Desa Candirejo Kecamatan Bawang Kabupaten Batang. Universitas Islam Negeri Walisongo Semarang. Khofifah, N. (2018). Tinjauan Hukum Islam Terhadap Sistem Pengupahan Buruh Emping Melinjo Di Desa Candirejo Kecamatan Bawang Kabupaten Batang. Universitas Islam Negeri Walisongo Semarang. Maesaroh, S. (2019). Tinjauan Hukum Islam Terhadap Praktik Upah Kerja Buruh Cangkul (Studi Di Kampung Argomulyo Kecamatan Banjit Kabupaten Way Kanan). Universitas Islam Negeri Raden Intan Lampung. Maesaroh, S. (2019). Tinjauan Hukum Islam Terhadap Praktik Upah Kerja Buruh Cangkul (Studi Di Kampung Argomulyo Kecamatan Banjit Kabupaten Way Kanan). Universitas Islam Negeri Raden Intan Lampung. Maulana, A. I. A. (2018). Penerimaan Upah Pekerja Harian Dalam Perspektif Hukum Islam ( Studi Kasus Para Pekerja Toko Pakaian Di Pasar Tengah Bandar Lampung ). Universitas Islam Negeri Raden Intan Lampung. Mega Salfina. (2021). Tinjauan Hukum Islam Terhadap Sistem Pengupahan Buruh Angkat Perahu Di Desa Klesem Kecamatan Kebonagung Kabupaten Pacitan. Institut Agama Islam Negeri Ponorogo. Nynda Kusuma Rachmi. (2020). Penerapan Ujrah Tenaga Kerja Industri Batik Di Desa Dinoyo Jatirejo Mojokerto. Universitas Islam Negeri Sunan Ampel Surabaya. Riski Ayu Distira. (2020). Praktek Upah Buruh Pembongkaran Ikan Di Pelabuhan Sibolga Ditinjau Dari Fiqh Muamalah. Institut Agama Islam Negeri Padangsidimpuan. Saiful Anwar. (2020). Tinjauan Hukum Islam Tentang Pembayaran Upah Buruh Setelah Kering Kopi (Studi Di Desa Ciptawaras Kecamatan Gedung Surian Kabupaten Lampung Barat). Universitas Islam Negeri Raden Intan Lampung.   Website Muthia, A. (2021). Geliat Batik Pekalongan di Masa Pandemi. Jatengdaily.com, https://jatengdaily.com/2021/geliat-batik-pekalongan-di-masa-pandemi/   Wawancara H.Eddywan, Pemilik Batik Larissa, Wawancara Langsung (3 September 2022). Castri, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Ipah, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Kasminah, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Ismael, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Yudi, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Rochim, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Ikhsan, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Nur, Buruh Produksi Kain Batik Larissa, Wawancara Langsung (3 September 2022) Fiki Arina, Pemilik Batik Feno, Wawancara Langsung (4 September 2022). Rasmini, Buruh Produksi Kain Batik Feno, Wawancara Langsung (4 September 2022) Siti, Buruh Produksi Kain Batik Feno, Wawancara Langsung (4 September 2022) Slamet, Buruh Produksi Kain Batik Feno, Wawancara Langsung (4 September 2022) Wawan, Buruh Produksi Kain Batik Feno, Wawancara Langsung (4 September 2022) Abdul, Buruh Produksi Kain Batik Feno, Wawancara Langsung (4 September 2022) Riyan, Buruh Produksi Kain Batik Feno, Wawancara Langsung (4 September 2022)   Artikel Jurnal Azzahra, M., Yohani, Y., & Fatah, K. (2023). ANALISIS DAMPAK SEBELUM DAN DI SAAT PANDEMI COVID-19 TERHADAP HARGA SAHAM DAN LABA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA. Jurnal Akuntansi STIE Muhammadiyah Palopo, 9(1), 1-14. Hakim, M. R., & Kholidah, N. (2020). Hak Merek Sebagai Jaminan Gadai Untuk Permodalan Umkm Industri Kreatif Kerajinan Batik. Pena Justisia: Media Komunikasi dan Kajian Hukum, 18(2). Hakim, M. R., & Kholidah, N. (2020). Hak Merek Sebagai Jaminan Gadai Untuk Permodalan Umkm Industri Kreatif Kerajinan Batik. Pena Justisia: Media Komunikasi dan Kajian Hukum, 18(2). Kholidah, N., & Salma, A. N. (2019). Filantropi kreatif: Pemberdayaan ekonomi umat berbasis zakat produktif pada program 1000 UMKM LAZISMU Kabupaten Pekalongan. Cakrawala: Jurnal Studi Islam, 14(2), 93-101. Rosanti, C. (2020). Faktor-Faktor yang Mempengaruhi Inovasi Produk Koperasi Jasa Keuangan Syariah Pada KJKS BTM Se Jawa Tengah. Jurnal Ilmiah Ekonomi Islam, 6(1), 8-13. Suyono, E., Farooque, O. A., & Riswan, R. (2016). Toward a model of traditional retailers and sellers empowerment in improving competitiveness against modern markets in Banyumas region, Indonesia. DLSU Business and Economics Review, 25(2), 147-165.